Can exploring natural recovery from substance misuse in psychosis assist with treatment? A review of current research. (July 2015) - Rebgetz, Shane; Kavanagh, David J.; Hides, Leanne
Abstract: Substance misuse in people with psychosis presents significant problems, but trials of treatments to address it show little sustained advantage over control conditions. An examination of mechanisms underpinning unassisted improvements may assist in the refinement of comorbidity treatments. This study reviewed existing research on natural recovery from substance misuse in people with psychosis. To address this issue, a systematic search identified only 7 articles that fulfilled the criteria. Their results suggest that people with psychosis report similar reasons to change as do non-psychotic groups, although they did not clarify whether the relative frequencies or priority orders were the same. Differences involved issues relating to the disorder and the functional problems faced by this group: receipt of treatment for mental health difficulties, worsening of mental health difficulties, and homelessness. The current research on reasons for change in people with psychosis is sparse and has significant limitations, and as yet it offers little inspiration for new treatments. A more fertile source may prove to be a detailed investigation of successful substance control strategies that are used in self-management by this group. Highlights: First review of the natural recovery literature in substance use and psychosis. People with psychosis report similar reasons to change as do users in the general population. Differences included change related to psychosis and improvement of basic needs.